A view from above - Boyd, Hugh (Wildfowl, 1996)
In 1888, Robert Browning rendered into English verse the story of The Pied Piper of Hamelin, about a strange man who offered to rid the German town of Hamelin of a plague of rats in the 14th Century. Having done so, he asked for his fee, which the mayor refused to pay. So the Piper played again and all the children of the town followed him into the hillside, never to be seen again. Browning's Piper was tall and thin and wore a 'queer long coat from heel to head...half of yellow nd half of red'. Peter Scott wasn't, and didn't. But he shared the Piper's more important characteristics. He was a leader, with a great capacity for gaining the confidence of animals and young people; the children of Hamelin followed the Piper because '...he led us, he said, to a joyous land, Joining the town and just at hand, Where waters gushed and fruit-trees grew, And flowers put forth a fairer hue, And everything was strange and new'; not bad as an adumbration of the Barn Elms development that is Peter's last and largest project.